Prevalence, Influence Factors and Cognitive Characteristics of Mild Cognitive Impairment in Type 2 Diabetes Mellitus - Li, Wei; Sun, Lin; Li, Guanjun; Xiao, Shifu (Frontiers in Aging Neuroscience, 2019)
Abstract Background Type 2 diabetes mellitus (T2DM) is considered as an independent risk factor for mild cognitive impairment (MCI). This study was performed to investigate the prevalence, influencing factors and cognitive characteristics of MCI in elderly patients with T2DM in China. Methods In the cross-sectional study, we performed cluster random sampling of 3246 people age 60 years and older across the country. All participants were interviewed and screened for T2DM and MCI. A total of 341 subjects were diagnosed of MCI according to the criteria of Petersen, and a total of 256 subjects were diagnosed of T2DM by using the American Diabetes association criteria Among the 256 T2DM people, 56 were also diagnosed with MCI. Logistic regression analyses were performed to evaluate risk and protective factor for MCI with T2DM. We also assessed their cognitive function by using the Mini-mental State Examination (MMSE), Montreal Cognitive Assessment (MoCA), Digit span, Associative learning test, Visual identification test, Verbal fluency, Wechsler Adult Intelligence Scale (WAIS)-III Block Design, Wechsler Adult Intelligence Scale (WAIS)-III picture completion and Auditory verbal learning test. Results Among the 256 T2DM patients, 56 were diagnosed with MCI, and the prevalence of MCI in T2DM was 21.8%. Multivariate logistic regression analyses showed that depression (p=0.002, OR=6.220, 95%CI: 2.005~19.290) was a risk factor for MCI among T2DM patients, while education (p<0.001, OR=0.869, 95%CI: 0.805~0.983) was a protective one. All the scores of neuropsychological tests (except for MMSE) in T2DM patients with MCI were lower than those without MCI (p<0.05), but there was no statistical difference(p>0.05) in neuropsychological tests between T2DM-MCI group and No-T2DM-MCI group. Linear regression analysis showed that the drug treatment of diabetes was positively correlated (t=2.263, p=0.025) with the total score of auditory word tests. Conclusions The present study suggests a high prevalence of MCI among Chinese T2DM patients. depression is a risk factors for MCI, while education is a protective one. T2DM patients with MCI often show comprehensive cognitive impairment, and the drug treatment of diabetes might help to improve cognitive function. Key words: T2DM, MCI, Chinese elderly, auditory verbal learning test